QUALITY OF LIFE , COMPLIANCE AND SATISFACTION FOR PATIENTS WITH PERITONEAL DIALYSIS AT QASSIM REGION IN KSA - Shereen A.Qalawa, Wafa A. AlQasem, Kholoud M. Alomeri (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background : Patients on dialysis live in a state-owned of prolonged stress are faced with a steady impression of death, diminish their life expectancies, tolerate a strict dietary schedule, and undergo disturbing treatments . The daily scuffle with end-stage renal disease symptoms and co morbidities, accompanied by the need to cope with psychosocial stressors, directly affects patients’ quality of life and mental health . Aim: To Identify quality of life , compliance and satisfaction for patients with peritoneal dialysis in Qassim region at Kingdom Saudi Arabia. Methods: A cross-sectional descriptive study design was used to conduct the study Convenience samples of 52 peritoneal Patients (male and females) were selected from conducted in dialysis centre in three of the King Fahd Specialist Hospital, Buraydah in the Qassim region, KSA . Tools of Data collection include four parts based on a review of relevant recent literature and adapted from Okpechi et al.,2013 and Fadem et al., 2011 regarding assessment of socio-demographic characteristics , investigation values and quality of life dimensions and compliance (physical, social, psychological , spiritual and educational ) and satisfaction level. Results: this study revealed that there was a highly significant relation between peritoneal patients satisfaction and their quality of life (p=0.001) in the items related to daily life and overall quality of life scores . while there are a significant relation were found between daily activities and quality of life (p=0.002, 0.013) in the items related to marital status respectively . Conclusions: There was a highly significant relation between patient's sociodemographic data and their quality of life in the items related to job type. While there are a significant relation were found between daily activities and quality of life in the items related to marital status, educational levels , job type and income levels .Recommendations: More researches to evaluate the effect of intervention program for more evidence that would be helpful for enhance patients 'adaptation and quality of life for peritoneal dialysis patients. Strengthening for implementing instructional scheme regarding peritoneal dialysis and its management in order to increase satisfaction and quality of life among those patients.